(3QSGdI aj GdaQGFVs - (3GdbQSgQj, GdbQTgQj, eMehOs
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg QH GdYGdejf hGdUdGI Ydi fHjg bGd GdfHj (B" (3e (B" (3JYdehG GdaQGFV hYdehgG ddfGS aEfgG fUa GdYde , jHOC ef JQcg GdejJ HGdJLgjRs
(3BNQgG (B:s
(3aUd aj Phj GdCQMGe hge ChdGO GdHfGJ hChdGO HfGJ GdGHf Ke GdCLOGO GdaGSOhf hGdLOGJ GdaGSOGJ Ke ChdGO GdCNhGJ hHfGJ GdCNhIs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3GdaQGFVs